Perancangan Video Company Profile Pada Prumajesty Agency Melalui Davinci Resolve 18 - Junaidi Kwok; Tony Wibowo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Video Company profile is one of the media to gain trust within the company. PruMajesty is one of the branches from Prudential that prioritize financial services. Background of this company is from examination and researcher’s interview about issue of gaining trust within the client. Writer has found the cause lack of trust between the company and the client. The research method will be using analyse descriptive with collecting data by observe and interview, after that creating video, preparing, executing, and discussion. Result of this society service will be the evidence of proving there’s an improvement between company and client so the process will be smooth, and amount of client has been increased by, number of views, client’s contact increasing. Based on the research result, and discussion chapter researcher given suggestions requires better communication so there won’t be ambiguous during the process, prioritize relationship between client and company.